SIMULATION OF SIDEMENTATION PREDICTION DUE TO GROWTH OF WATER BIOMASS ' ECENG GONDOK ' IN LAKE BUYAN BULELENG BALI - Aris Gunadi; Dewi Oktofa Rachmawati (JURNAL ILMU KOMPUTER INDONESIA, 2021)
Buyan Lake, is one of the caldera lakes originating from an ancient volcanic eruption in Bali. Geographically, Lake Buyan is located in Pancasari Village, Sukasada District, Buleleng Regency. The existence of this lake is very important for the surrounding community. This lake is a source of drinking water, tourism, agriculture for the people in Buleleng Regency. One of the factors that influence the existence of Lake Buyan is the uncontrolled growth of water biomass (Eceng Gondok)  is influenced by fishing and agricultural activities that produce nitrite and phosphate. 10 individuals of eceng gondok can grow to 600000 individuals within 8 months. The relationship of the number of cementations (Ton) to the area covered by eceng gondok  (Ha) is expressed by the relationship y = 0.25 x -11,525. The sedimentation prediction simulation model is carried out by taking conditions in 2020, in Lake Buyan there are 8 JKA (Floating Cage Net) stations, the value of nitrite and phosphate growth rates for each station, and the growth of fishery activity is 1%. It was found that the sedimentation deposits showed a significant effect which caused the shrinkage of Lake Buyan. Sedimentation  in 2020 are still around 0.48 tons, but in 2050 the annual will be 40.34 tons. This causes the shrinkage of Buyan Lake in 2020 which is still 370 Ha, but in 2050 only 31 Ha.